Allergy transcription before and after the implementation of an inpatient electronic prescribing system in a tertiary referral hospital: a case study in two oncology wards - Launders,H; Jacklin,A; Franklin,BD (Safety in Health, 2015)
BackgroundPatients with allergies can be protected from potentially life threatening harm by recording their allergen and reaction correctly. Electronic prescribing is being widely implemented with a view to improving patient safety; decision support functions can alert prescribers to the risk of prescribing an allergen. However the allergen must be correctly recorded to utilize this functionality. This study aimed to explore whether the introduction of an inpatient electronic prescribing system, in place of paper-based prescribing, has affected the accuracy of transfer of allergen data between hospital documentation systems.MethodsRetrospective case note review of a random sample of 100 patients admitted to two oncology wards in a UK hospital before implementation of electronic prescribing, and 100 admitted afterwards. We compared accuracy of allergy information transcribed from admission documentation to the inpatient prescribing system and then to the separate electronic discharge summary for paper-based versus electronic inpatient prescribing. We analyzed data separately for patients with no known drug allergy and those with a recorded allergen.Results There was no difference between prescribing systems in the transfer of ‘no known drug allergy’ status from the admission documentation to the inpatient prescribing record. However transfer of ‘no known drug allergy’ status was better on electronic discharge summaries prepared from the separate electronic inpatient system (transferred correctly for 58 of 72 discharges, 81%) when compared with paper inpatient prescriptions (26 of 68 patient discharges, 38%) p<0.001.For patients with an allergy the correct transfer of allergens from admission documentation to the inpatient prescribing record was lower for the electronic prescribing system (10 of 28 patient admissions, 36%) when compared with paper prescribing (21 of 32 patient admissions, 66%) p=0.02. However correct transfer of aller